Transmission of Bacterial Symbionts With and Without Genome Erosion Between a Beetle Host and the Plant Environment - Wierz, Jürgen C.; Gaube, Paul; Klebsch, Dagmar; Kaltenpoth, Martin; Flórez, Laura V. (Frontiers in Microbiology, 2021)
Many phytophagous insects harbor symbiotic bacteria that can be transmitted vertically from parents to offspring, or acquired horizontally from unrelated hosts or the environment. In the latter case, plants are a potential route for symbiont transfer and can thus foster a tripartite interaction between microbe, insect and plant. Here we focus on two bacterial symbionts of the darkling beetle Lagria villosa that belong to the genus Burkholderia; the culturable strain B. gladioli Lv-StA and the reduced-genome strain Burkholderia Lv-StB. The strains can be transmitted vertically and confer protection to the beetle’s eggs, but Lv-StA can also proliferate in plants, and both symbiont strains have presumably evolved from plant pathogens. Notably, little is known about the role of the environment for the transmission dynamics and the maintenance of the symbionts. Through manipulative assays, we demonstrate transfer of the symbionts from the beetle to wheat, rice and soybean plants, as well as leaf litter. In addition, we confirm that aposymbiotic larvae can pick up Lv-StA from dry leaves and the symbiont can successfully establish in the beetle’s symbiotic organs. Also, we show that the presence of plants and soil in the environment improves long-term symbiont maintenance. These results indicate that the symbionts of L. villosa beetles are still capable of interacting with plants despite signatures of genome erosion and suggest that a mixed-mode of bacterial transmission is likely key for the persistence of the symbiosis.